2021
DOI: 10.2337/dc20-3128
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Type 1 Diabetes in Children and Adolescents: A Meta-analysis

Abstract: BACKGROUND There is substantial evidence that adults with type 1 diabetes have reduced bone mineral density (BMD); however, findings in youth are inconsistent. PURPOSE To perform a systematic review and meta-analysis of BMD in youth with type 1 diabetes using multiple modalities: DXA, peripheral quantitative computed tomography (pQCT), and/or quantitative ultrasound (QUS). DAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…A Korean study ( 27 ) found that obese children and adolescents with T2D had significantly lower BMD Z-scores at the femoral neck compared with age-, sex-, and BMI-matched controls. A meta-analysis ( 28 ) also indicated that children and adolescents with type 1 diabetes (T1D) had lower BMD than controls. Hence, peak bone mass in youth with prediabetes and diabetes might be influenced by the deterioration of bone mineral accruals.…”
Section: Discussionmentioning
confidence: 99%
“…A Korean study ( 27 ) found that obese children and adolescents with T2D had significantly lower BMD Z-scores at the femoral neck compared with age-, sex-, and BMI-matched controls. A meta-analysis ( 28 ) also indicated that children and adolescents with type 1 diabetes (T1D) had lower BMD than controls. Hence, peak bone mass in youth with prediabetes and diabetes might be influenced by the deterioration of bone mineral accruals.…”
Section: Discussionmentioning
confidence: 99%
“…Higher body fat may also relate to the skeletal deficits in children with T1D (9). Children with T1D have lower bone mass (i.e., mineral content and areal bone mineral density) along with altered trabecular density and micro-architecture (e.g., trabecular thickness) according to meta-analyses (43)(44)(45). Recent evidence suggested that body fat % was negatively associated with total body bone mineral content and areal bone mineral density in children (9).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicate that the BMD of T1DM patients is reduced, while the BMD of T2DM patients is controversial [18,19]. Additionally, the hip fracture risk of T1DM is twofold-fivefold of the T2DM patients [20].…”
Section: Discussionmentioning
confidence: 99%